1998
DOI: 10.1093/hmg/7.7.1179
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Retinal Guanylate Cyclase (RETGC-1) Gene in Dominant Cone-Rod Dystrophy

Abstract: The dominant cone-rod dystrophy gene CORD6 has previously been mapped to within an 8 cM interval on chromosome 17p12-p13. The retinal-specific guanylate cyclase gene (RETGC-1), which maps to within this genetic interval and previously was implicated in Leber's congenital amaurosis, was screened for mutations within this family and in a panel of small families and individuals with various cone and cone- rod dystrophy phenotypes. A missense mutation (E837D) was identified in affected members of the CORD6 family,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(126 citation statements)
references
References 33 publications
4
120
0
Order By: Relevance
“…CORD6 is typically diagnosed as an early-onset blinding disorder, frequently by 7 years of age, first as impaired central and color vision (cone function), later involving rods, by progressing to the peripheral visual field with age (34,35). Among the genes linked to CORD6 in multiple genetic studies (34,45,51,52), GUCY2D coding for a human RetGC1 has been found most frequently affected by substitutions in codon 838 replacing , were shown to cause a prominent shift in Ca 2ϩ sensitivity of the cyclase regulation by GCAP1 when heterologously expressed in cultured HEK293 (44 -46).…”
Section: The Arg 838 Mutation In Retgc1 Alters Physiology Of Photorecmentioning
confidence: 99%
See 1 more Smart Citation
“…CORD6 is typically diagnosed as an early-onset blinding disorder, frequently by 7 years of age, first as impaired central and color vision (cone function), later involving rods, by progressing to the peripheral visual field with age (34,35). Among the genes linked to CORD6 in multiple genetic studies (34,45,51,52), GUCY2D coding for a human RetGC1 has been found most frequently affected by substitutions in codon 838 replacing , were shown to cause a prominent shift in Ca 2ϩ sensitivity of the cyclase regulation by GCAP1 when heterologously expressed in cultured HEK293 (44 -46).…”
Section: The Arg 838 Mutation In Retgc1 Alters Physiology Of Photorecmentioning
confidence: 99%
“…Among the genes linked to CORD6 in multiple genetic studies (34,45,51,52), GUCY2D coding for a human RetGC1 has been found most frequently affected by substitutions in codon 838 replacing , were shown to cause a prominent shift in Ca 2ϩ sensitivity of the cyclase regulation by GCAP1 when heterologously expressed in cultured HEK293 (44 -46). However, the physiological effects of the Arg 838 substitutions in RetGC1 have not been demonstrated in mammalian photoreceptors.…”
Section: The Arg 838 Mutation In Retgc1 Alters Physiology Of Photorecmentioning
confidence: 99%
“…2,3 Sixty RP causative gene mutations were found. 4 EYS is an important and common cause of RP in the Japanese, Spanish, British, Chinese, Israelis, and Palestinians.…”
Section: Introductionmentioning
confidence: 99%
“…A dominant form of cone-rod dystrophy (CORD6) is associated with GC-E mutations in humans [201], and a naturally occurring null mutation in the chick GC-E gene causes autosomal recessive retinal degeneration [202]. These findings are related to the phenotype of GC-E null mice [199].…”
Section: Gc-e Null Micementioning
confidence: 99%